2011
DOI: 10.1111/j.1574-6941.2011.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure in methane hydrate-bearing sediments of freshwater Lake Baikal

Abstract: Gas hydrates in marine sediments have been known for many years but recently hydrates were found in the sediments of Lake Baikal, the largest freshwater basin in the world. Marine gas hydrates are associated with complex microbial communities involved in methanogenesis, methane oxidation, sulfate reduction and other biotransformations. However, the contribution of microorganisms to the formation of gas hydrates remains poorly understood. We examined the microbial communities in the hydrate-bearing sediments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 49 publications
1
31
0
7
Order By: Relevance
“…The Dehalococcoidales (Chloroflexi [65, 66]) and the Miscellaneous Crenarchaeotic Group (MCG, [67, 68]) are promising candidates for such hybrid forms of energy harvesting and were among the most influential lineages in our data set (Additional file 4). The MCG co-occurred with Dehalococcoidales, similar to what was found in methane hydrate-bearing sediment in Lake Baikal at >1500-m water depth [69]. Another indication that biotic interactions are important in Lake Stechlin sediments is the appearance of the Candidatus Parvarchaeum as a structuring lineage (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The Dehalococcoidales (Chloroflexi [65, 66]) and the Miscellaneous Crenarchaeotic Group (MCG, [67, 68]) are promising candidates for such hybrid forms of energy harvesting and were among the most influential lineages in our data set (Additional file 4). The MCG co-occurred with Dehalococcoidales, similar to what was found in methane hydrate-bearing sediment in Lake Baikal at >1500-m water depth [69]. Another indication that biotic interactions are important in Lake Stechlin sediments is the appearance of the Candidatus Parvarchaeum as a structuring lineage (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Metagenomic analysis [39] has been used to evaluate the diversity of microorganisms in marine ecosystems [40][44], thermal springs [45], [46], and fresh water bodies [47], including sites with gas hydrate-bearing sediments in Lake Baikal [48].…”
Section: Introductionmentioning
confidence: 99%
“…Community structure of bacteria, archaea and viruses, in the deep and anoxic sediments of the volcanic Lake Pavin (France) gradually changed with depth and some showed exceptional morphotypes . The microbial assemblages in the hydratebearing sediments of Lake Baikal showed that shallow sediments were dominated by Archaea, deeper sediments located at 8590 cm depth close to the hydrate were dominated by bacteria, consistent with the biological origin of methane hydrates in Lake Baikal (Kadnikov et al, 2012). The examination of Acidobacteria in freshwater ponds at Doana National Park (southwestern Spain) showed that in oxygen-saturated areas in the sediment surface, around 4% of total bacterial RNA belonged to Acidobacteria (Zimmermann et al, 2012).…”
Section: Nuisance Bloom Forming and Harmful Algaementioning
confidence: 56%